PREFACE, TABLE OF CONTENTS, & ACKNOWLEDGMENTS - Herdiansyah, Herdis (UI Scholars Hub, 2019)
The development of the world demands changes in the environment from time to time, and this condition can not be avoided, for that the academic world is required to always be ready and watchful for this condition. This challenge makes the Journal of Environmental Science and Sustainable Development (JESSD) continue to be consistent with the focus of environmental studies until now. Starting with the inaugural edition in 2018, JESSD continues to be aware and focus on environmental studies and sustainable development in developing countries, especially for Southeast Asia countries. In this issue of Volume 2 Issue 1, we present eight scientific articles from various parties, with various studies on the environment and sustainable development. The authors of these eight articles came from various universities namely Kyoto University (Kyoto, Japan), Musamus University (Merauke), Bogor Agriculture University (Bogor), Universitas Pelita Harapan (Tangerang), and Universitas Indonesia (Jakarta); and from one of the government agencies, that is The Geospatial Information Agency (Cibinong, West Java)